Fluorodynamers Displaying Tunable Fluorescence on Constitutional Exchanges in Solution and at Solid Film–Solution Interface. Issue 45 (10th July 2020) - Si, Mingran; Zhu, Weijia; Zhang, Yan; Barboiu, Mihail; Chen, Jinghua
Abstract: Dynamic covalent polymers—dynamers—are adaptive materials that offer timely variant adaptive macroscopic organization across extended scales. In the current study, imine exchange reactions and fluorescence transfer can occur at the interfaces between various solutions and solid state dynameric films. The fluorescence quenching upon imine formations for designed fluorogen was successfully demonstrated, and this tunable fluorescence was further used to study the re‐composition of a solid film. Moreover, the dynamic covalent films also exhibited responsiveness to competing amines and acid/base conditions, both in solutions and solid film–solution interface. This work can provide more insights into interface dynamic chemistry and holds great potential for further applications in optical and biomedical materials. Abstract : On firm ground : Solid films constituting dynamic covalent fluorodynamers have been designed and used to analyse the interface imine exchange reactions between solid–solution interface, leading to re‐composition and tunable fluorescence in response to competing amines and acid/base conditions.